Analysis Of Work Motivation Factors In Increasing Work Productivity In Regional Financial And Asset Management Agency, Sarmi District, Papua Province - Moch Resky Iskandar (Economy Deposit Journal (E-DJ), 2022)
This study aims to determine the effect of motivation in the form of material incentives on increasing employee work productivity at the Regional Financial and Asset Management Agency, Sarmi Regency, Papua Province. The type of research used is descriptive quantitative, in which the writer describes the results of observations and analyzes the data obtained in the field. The data analysis used in this study is descriptive analysis by explaining the material motivation of the incentives provided by the company to employees to increase work productivity at the Regional Financial and Asset Management Agency, Sarmi Regency, Papua Province After analyzing and discussing the problem, the authors conclude that motivation for increasing work productivity is very influential by the remuneration provided which can be adjusted to the conditions of the agency concerned, because with motivation and a sense of belonging and great responsibility, it will increase work productivity and increase productivity. income for the Regional Financial and Asset Management Agency, Sarmi Regency, Papua Province, so that it has an impact on the welfare of employees and will support the achievement of goals in agencies that have been planned as effectively and efficiently as possible. To increase employee motivation and work productivity, the head of the Regional Financial and Asset Management Agency, Sarmi Regency, Papua Province, applies work discipline, namely the stipulation of working hours and limits on working hours accompanied by breaks. Policies in increasing motivation for employee work productivity, which need to be considered especially the provision of remuneration, discipline and other prizes as well as Eid gifts Keywords: Work Motivation, work productivity.